The Implementation of Dynamic Records Management Policy - Rizki Fillya Curtinawati (FISIP UWP, 2022)
Archive management in universities is an obligation contained in Law no. 43 of 2009 concerning Archives. Pawyatan Daha University as an organization engaged in the field of education one of its administrative activities is to carry out the filing process carried out by the Bureau of Academic Administration, Student Affairs and Alumni (BA2AK). The purpose of this study was to identify and describe the implementation of active dynamic archive management in improving public services at the Bureau of Academic Administration, Student Affairs and Alumni (BA2AK) based on Law no. 43 of 2009 concerning Archives. This type of research uses descriptive research with a qualitative approach. The results of this study are that the Implementation of Dynamic Archive Management in the Bureau of Academic Administration, Student Affairs, and Alumni (BA2KA) Pawyatan Daha University based on Law no. 43 of 2009 concerning archive management has not run optimally. This is because the results of the analysis of the 4 stages of management contained in Law no. 43 of 2009 concerning archive management has been implemented but each of these stages is not running optimally. There are still many shortcomings at each stage for archive management, especially at the storage and retrieval stage. Storage and retrieval, most of which still have an impact on the lack of ineffective and efficient archive management, so it is necessary to improve digital management